A Trial to Predict the Diurnal Global Solar Irradiance Received On A Horizontal Plane for Clear Days in Terms of The Solar Angles. - Shaban, Samia Sayed (JOURNAL OF ADVANCES IN PHYSICS, 2019)
A general distribution function is suggested to predict both symmetrical and asymmetric diurnal global solar irradiance q (t) W/m2 received on a horizontal surface, where “t” is the local day time "h" .The distribution is given in terms of well-established parameters, namely: td :- the length of the solar day expressed in term of the solar angles. tmax :- the time of the day at which the irradiance reaches its maximum value qmax W/m2 for symmetrical distribution tmax = i.e. it occurs at the midday time. td , tmax and qmax are taken as parameters. The suggested expression can be easily integrated along the length of the day time. This gives the daily totals of the received solar energy per unit horizontal area.This is of vital technical importance for solar energy exploitations and applications. Comparison between computed according to the present model and published experimental meteorological data in Barcelona (Spain), Hong Kong (China), Jeddah and Makah (Saudi Arabia) is given as illustrative examples. Comparison with the published trials for the same locations is also clarified. The introduced model itself gives good fitting for the intermediate interval points of the local day time which is the more effective region.